RESTRICTIONS ON DIVORCE PROCEDURES IN SEMA NO. 3 OF 2023: BETWEEN LEGAL CERTAINTY AND THE IMPLEMENTATION OF MAQASID SHARIA IN INDONESIA - Faroby, Dardena Betarania (Universitas Nurul Jadid, 2025)
This article analyses the restrictions on divorce procedures in Supreme Court Circular Letter (SEMA) Number 3 of 2023 from the perspective of legal certainty and maqasid al-syari’ah particularly those that occurred at the Pengadilan Agama Barru. This policy requires proof of continuous disputes and quarrels accompanied by a minimum separation period of six months as a prerequisite for the granting of a divorce. This study uses a normative legal research method with a legislative, conceptual, and case approach, and is analysed qualitatively through the theory of legal certainty and the framework of maqasid al-syari’ah. The findings show that the six-month restriction serves as an objective parameter that reinforces the principle of making divorce difficult and increases the consistency of evidence in religious court practice. However, its implementation is not mechanistic, as judges still exercise discretion in assessing concrete facts, including exceptions for cases of domestic violence. From a maqasid perspective, this policy is in line with the objectives of preserving offspring and family stability (hifz al-nasl), as long as its application does not neglect the protection of life (hifz al-nafs). This study contributes empirically by showing that administrative judicial policies have a real impact on adjudicative practice while opening up a dialectic between legal certainty and public interest in Islamic family law in Indonesia.